How do you simplify 9(2z+6)+(z+3)+3(10z+12)9(2z+6)+(z+3)+3(10z+12)?

2 Answers

9(2z+6)+(z+3)+3(10z+12)=49z+939(2z+6)+(z+3)+3(10z+12)=49z+93

Explanation:

9(2z+6)+(z+3)+3(10z+12)9(2z+6)+(z+3)+3(10z+12)
=9xx2(z+3)+(z+3)+3xx2(5z+6)=9×2(z+3)+(z+3)+3×2(5z+6)
=18(z+3)+(z+3)+6(5z+6)=18(z+3)+(z+3)+6(5z+6)
=19(z+3)+6(5z+6)=19(z+3)+6(5z+6)
=19z+19xx3+6xx5z+6xx6=19z+19×3+6×5z+6×6
=19z+57+30z+36=19z+57+30z+36
=19z+30z+57+36=19z+30z+57+36
9(2z+6)+(z+3)+3(10z+12)=49z+939(2z+6)+(z+3)+3(10z+12)=49z+93

49z+9349z+93

Explanation:

  • Expand out the brackets
    18z+54 +z+3 +30z+3618z+54+z+3+30z+36
  • Put similar subjects together
    18z + z + 30z + 54 + 3 + 3618z+z+30z+54+3+36
  • Add together
    49z + 9349z+93